2020
DOI: 10.1177/2309499020915797
|View full text |Cite
|
Sign up to set email alerts
|

Management of comminuted mid-shaft clavicular fractures: Comparison between dual-plate fixation treatment and single-plate fixation

Abstract: Background: We consider dual-plate fixation to improve construct rigidity in cases with fracture complexity. The purpose of this study is to compare the rate of nonunion, prognosis, and complications at 6–12 months for surgically treated acute mid-shaft clavicle fractures when extra-periosteal dual-plate fixation is used in place of the conventional single-plate fixation. Materials and Methods: The comparative study was conducted on 47 patients who received acute mid-shaft clavicular fracture treatment in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Included studies were published between 2011 and 2020, and all studies were retrospective in nature. Five of the studies were retrospective cohort studies, 11,13,14,16,17 and three were case series. 7,12,15 Of the included studies, five reported on patients surgically treated with only mini-fragment plates, 7,12e14,17 and three included patients treated with dual plate fixation consisting of a combination of mini-fragment and smallfragment plates (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies were published between 2011 and 2020, and all studies were retrospective in nature. Five of the studies were retrospective cohort studies, 11,13,14,16,17 and three were case series. 7,12,15 Of the included studies, five reported on patients surgically treated with only mini-fragment plates, 7,12e14,17 and three included patients treated with dual plate fixation consisting of a combination of mini-fragment and smallfragment plates (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…7,12,15 Of the included studies, five reported on patients surgically treated with only mini-fragment plates, 7,12e14,17 and three included patients treated with dual plate fixation consisting of a combination of mini-fragment and smallfragment plates (Table 1). 11,15,16 The mean age of patients was 36.0 years and the majority were male (n ¼ 201; 79.8%). Patients were followed post-operatively for a mean of 8.3e35.0 months.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardware removal occurred in 4.4% (N ¼ 318) and 12.3% (N ¼ 309) of patients undergoing dual and single plate fixation, respectively. Among the four comparative studies, 45,46,49,51 dual plating resulted in a 77% lower odds of hardware removal compared to single plate fixation (OR, 0.23; 95% CI, 0.07 to 0.78; P ¼ 0.02) (Figure 2 29 2.7-mm superior and 2.4-mm antero-inferior mini-fragment plates 3.5-mm superior or antero-inferior locking reconstruction plate Qamar et al 30 Two 3.5-mm one-third semi-tubular plates -Shannon et al 31 One-third tubular, one-quarter tubular or 2.0-mm superior or anterior mini-fragment plates with 2.7-mm or 3.5-mm pelvic reconstruction plates or 3.5-mm superior locking compression plate -Zhuang et al 52 3.5-mm superior locking compression plate or reconstruction plate and anteroinferior mini-fragment ''aid plate'' 3.5-mm antero-inferior locking compression plate S Sheth et al…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…[ 1 ] In the past, non-surgical treatment has been preferred for axial clavicular fractures because of the extremely low rate of bone nonunion, even in the case of significant displacement. [ 2 , 3 ] However, a number of scholars have recently found that nonoperative displaced fractures have a higher rate of nonunion than previously reported. At present, a consensus has been reached on the non-surgical treatment of undisplaced central clavicle fractures.…”
Section: Introductionmentioning
confidence: 99%